Quality perception and satisfaction of the customers toward the counter services of the public sector / Neder Safwan - Safwan, Neder (2016)
The purpose of this study is to identify the effect of service quality dimension (SERVQUAL model) towards customer satisfaction One Serve Kuala Lumpur City Hall counter. The five dimension of SERVQUAL have been influence on customer satisfaction. The five dimensions are tangible, reliability, responsiveness, assurance and empathy as the independent variables while for the dependent variable is customer satisfaction. This research have been improved by questionnaire for the purpose of data collection and distributing it to 100 respondent and the questionnaire were filled up by the customers who come to One Serve counter.